Association between iron deficiency anaemia and simple febrile seizure in South Indian rural population - Durai, Gayathri; Parambath, Syamily; Ramayi, Rajendiran Ramachari (International Journal of Contemporary Pediatrics, 2020)
Background: Simple febrile seizure is a common problem worldwide, many studies have investigated the etiology and natural history of febrile seizures and evaluated various management strategies, but very little information is available about iron deficiency as a risk factor. Hence, we aimed to determine the association between iron deficiency anaemia and simple febrile seizures in south Indian rural population. Methods: It is an observational study done in paediatrics department at Sri Venkateshwaraa medical college hospital and research centre. A total 120 (60 cases and 60 control) were included in the study. Children with febrile seizures and controls were included fever without seizures. Informed consent was taken from parents of each child. Children were divided into two groups, cases and controls. Serum ferritin level, Hb, HCT and MCV levels were assessed. Results: Mean Hb level in cases and controls were 9.1±1.2 and 12.7±1.7 mg/dl respectively. Mean MCV value in cases and controls was 78.1±6.2 and 81.4±6.9 respectively. Mean serum iron level in cases was 29.9±4.9 and in controls mean serum iron level was 42.8±7.4. Conclusions: Iron deficiency anaemia is considered as a risk factor for febrile seizures in children.